MATHEMATICAL MODELING OF ELECTROCHEMICAL PROCESSES IN LITHIUM-ION BATTERIES POTENTIALLY STREAMING METHOD - S. P. Halutin; B. V. Zhmurov; I. E. Starostin (Научный вестник МГТУ ГА, 2016)
Mathematical models in the electrical parameters of physico-chemical processes in lithium-ion batteries are developed. The developed model parameters (discharge mode) are identified out of family of discharging curve. By using of the parameters of this model we get the numerically model of lithium-ion battery.